Thoughts on student mobility: Why Japanese students are more “immobile”. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2009)
Once a Western researcher called Japan’s education system as “immobilist” (Shoppa, 1991) describing conspicuously incremental education reform processes. Now the number of Japanese university students studying abroad has been on the gradual decline since 2004, showing another kind of immobility (OECD, 2008).